Neoliberal gothic : international gothic in the neoliberal age - Blake, Linnie; Monnet, Agnieszka Soltysik (Manchester University Press, 2017)
The explosion of interest in the gothic in recent years has coincided with a number of seismic political changes that have reshaped the world as we know it. 'Neoliberal Gothic' explores that world, considering the ways in which the exponential increase in the cultural visibility of the gothic attests to the mode's engagement with the most significant dynamics of our age. These include the triumph of free market economics, the revolution in information and communication technologies, the emergence of global biotechnologies, the increasing power of transnational corporations, the US-led 'War on Terror' and the global financial crisis of 2008. Through analysis of texts drawn from literature, film, television, theatre and the visual arts (from the Europe to South East Asia, Africa to North and South America) the collection examines the ways in which the representational strategies of the gothic mode are ideally suited to an exploration of the dark side of neoliberal enterprise.
Keywords: Gothic fiction (Literary genre) -- History and criticism.; Neoliberalism.; Gothic literature -- History and criticism.; Néo-libéralisme.; Littérature gothique -- Histoire et critique.; Society and social sciences.; Cultural studies.; LITERARY CRITICISM -- Gothic & Romance.; Neoliberalism; Gothic literature; Gothic fiction (Literary genre); Biography, Literature & Literary studies.; Electronic books; Criticism, interpretation, etc.